2016
DOI: 10.3390/md14120230
|View full text |Cite
|
Sign up to set email alerts
|

Biological Potential of Chitinolytic Marine Bacteria

Abstract: Chitinolytic microorganisms secrete a range of chitin modifying enzymes, which can be exploited for production of chitin derived products or as fungal or pest control agents. Here, we explored the potential of 11 marine bacteria (Pseudoalteromonadaceae, Vibrionaceae) for chitin degradation using in silico and phenotypic assays. Of 10 chitinolytic strains, three strains, Photobacterium galatheae S2753, Pseudoalteromonas piscicida S2040 and S2724, produced large clearing zones on chitin plates. All strains were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 59 publications
(66 reference statements)
2
21
0
5
Order By: Relevance
“…JC28, many P. piscicida strains have also shown strong inhibition against vibrios and other bacterial pathogens (39,40) and antifungal activity against several fungi, including Arthrinium c.f. saccharicola (41) and Fusarium oxysporum (42). P. piscicida strains have also demonstrated eukaryotic toxicity, killing Artemia nauplii brine shrimp and Caenorhabditis elegans nematodes (43), and lysing Gymnodinium catenatum algal cells (44).…”
Section: Discussionmentioning
confidence: 99%
“…JC28, many P. piscicida strains have also shown strong inhibition against vibrios and other bacterial pathogens (39,40) and antifungal activity against several fungi, including Arthrinium c.f. saccharicola (41) and Fusarium oxysporum (42). P. piscicida strains have also demonstrated eukaryotic toxicity, killing Artemia nauplii brine shrimp and Caenorhabditis elegans nematodes (43), and lysing Gymnodinium catenatum algal cells (44).…”
Section: Discussionmentioning
confidence: 99%
“…In bacteria, the majority of chitinases belong to glycosyl hydrolase (GH) family 18 (25). Recently, chitinases belonging to GH family 19 have been discovered in a few groups of prokaryotes (2630), and we have found that the genomes of 10 marine chitinolytic bacteria, including Pseudoalteromonas , all contain at least one GH19 chitinase (31).…”
Section: Introductionmentioning
confidence: 92%
“…Although the chitinolytic activity of some species has been reported in the literature, it remains unknown which group of microorganisms is the most effective at decomposing this polymer. Several authors have reported marine ecosystems as a main source of chitinase-producing microorganisms, mainly bacteria (Sara et al, 2016; Swiontek et al, 2014; Suresh, 2012). Chitinolytic bacteria represent only 4% of the currently known bacteria (Swiontek et al, 2014).…”
Section: Introductionmentioning
confidence: 99%